Lipidomic Analysis to Assess the Correlation between Ceramides, Stress Hyperglycemia, and HbA1c in Acute Myocardial Infarction - Melania Gaggini; Elena Michelucci; Rudina Ndreu; Silvia Rocchiccioli; Kyriazoula Chatzianagnostou; Sergio Berti; Cristina Vassalle (Molecules, 2023)
Ceramides have been associated with cardiometabolic disease (e.g., acute myocardial infarction (AMI) and type 2 diabetes (T2D)) and adverse outcomes. Acute admission hyperglycemia (AH) is a transient glucose alteration in response to stress. As glycated hemoglobin (HbA1c) reflects the glycemia over a longer period of time, its use may be helpful in distinguishing between the AH and hyperglycemia associated with T2D in the AMI setting. The aim was to assess the correlation of ceramides with both AH (defined as an admission glucose level ≥140 mg/dL in the absence of T2D) and HbA1c-T2D and other demographic, clinical, and inflammatory-related biomarkers in AMI. High-performance liquid chromatography–tandem mass spectrometry was used to identify nine ceramide species, and their three ratios, in 140 AMI patients (FTGM coronary unit, Massa, Italy). The ceramides did not correlate with stress hyperglycemia, but specific species were elevated in T2D-AMI. Moreover, some ceramides were associated with other cardiometabolic risk factors. Ceramides assessment may be helpful in better understanding the pathogenic molecular mechanisms underlying myocardial acute events and cardiometabolic risk, as a basis for the future evaluation of their role as prognostic predictors and therapeutic targets in T2D-AMI patients.